Periodontal Disease and Pregnancy Hypertension: A Clinical Correlation. Issue 8 (1st August 2013) - Pralhad, Swati; Thomas, Betsy; Kushtagi, Pralhad
Abstract : Background: Periodontal disease is thought to be associated with increased risk of systemic diseases and adverse pregnancy outcomes, including pregnancy hypertension (PH). The aim of the present study is to find the prevalence of periodontal disease in females with PH in a rural‐based medical institute. Methods: The present case control study was performed with 200 females, 100 with PH and 100 without PH. Antenatal periodontal screening was performed within 72 hours of their hospital admission for delivery. The periodontal parameters assessed were oral hygiene index–simplified, gingival index, mean probing depth, and loss of attachment. Results: Prevalence of periodontal disease was 65.5% and was significantly higher ( P <0.0001) in females with hypertension (relative risk = 1.5; 95% confidence interval [CI] = 1.3 to 1.9). Socioeconomic status, education, occupation, and body mass index did not appear to influence the relationship between periodontal disease and PH on bivariate multiple logistic regression analysis. Nulliparous females were at higher odds to develop periodontal disease and PH (odds ratio = 1.7; 95% CI = 0.5 to 6.1). As the severity of periodontal disease increased from moderate to severe, the severity of hypertension also increased ( r 2 = 0.8 and 0.5 for moderate and severe periodontal disease, respectively). Conclusion: Periodontal disease is more prevalent in females with PH.